Revisiting Public-Private Partnerships in the Power Sector - Vagliasindi, Maria (World Bank, 2015)
Given the chronic power shortages faced by numerous developing countries, and the need everywhere to keep pace with demand, understanding the drivers of public private partnerships (PPPs) in energy is critical. While many private electricity projects have been delayed and financing costs have increased, the impact of the global financial crisis was less severe than that of previous crises that originated in developing countries. This resilience stems from developing countries? need to expand generation capacity, electricity sector reforms and better regulatory frameworks, and short-term solutions (such as rental power plants).